(untitled) (Journal of the College of Basic Education, 2022)
Aims current research to know the effect of atypical Marzano cycle seven-learning in the collection of history at the fifth grade literary students and their attitude toward material formed the research sample of 108 students were selected Qsidia from junior high (Farabi) affiliated to the General Directorate for Educational Second Karkh for the academic year (2014 -2015)They were spread over three equal groups by 35 students in the first experimental group taught strategy Marzano, while the second experimental group were 36 students studying strategy and the cycle of Seven learning, either the third group, a control group hits (34) students are taught the usual way, was coined researcher (30) paragraph of multi-type test and after the honesty of the test specifications after a presentation to a group of experts and got (80%), and at a rate stability (80%) and rewarded researcher three groups in a number of variables, namely, (intelligence, previous information, The educational attainment of parents) The researcher found the following results: 1-superiority of the second experimental group taught Bonmozj learning cycle sevenfold on the first group, which is studying Bonmozj Marzano in the collection and direction. outweigh the second experimental group and the first by considering the Models of the learning cycle of Seven and Marzano to the control group, who studied in the traditional way in the collection and direction.